Spatial Variability of Land Use Changes Due to JJLS (Southern Cross Road Network) Development in Kulon Progo Regency in 2016, 2020, and 2024 - Muwahhid, Ali; Hizbaron, Dyah Rahmawati; Mutaqin, Bachtiar Wahyu (Universitas Lampung, 2025)
The construction of the JJLS (Southern Cross Road Network) project in Kulon Progo Regency passes through Kapanewon Galur, Panjatan, Wates, and Temon to connect the Provinces of DIY and Central Java. The development of JJLS infrastructure can lead to the development of residential land and other functional buildings in the surrounding areas (Hendry, 2021). This study attempts to determine changes in land use variability due to the construction of JJLS in Kulon Progo Regency. Based on this information, changes in land use that occur intensively in certain areas can be monitored and detected early, so that appropriate policies can be formulated to prevent uncontrolled changes in land use. The research method used in this study is the interpretation of digital sentinel 2 imagery, which is then overlayed with a land use map to determine land changes that occurred in 2016, 2020 and 2024. Statistical analysis was carried out to determine the effect of JJLS development on land use changes in Kulon Progo Regency, especially in the sub-districts through which JJLS passes. The results of the study showed that there were significant changes in land use in the range of 2016, 2020 and 2024. Based on the results of the RCI calculation in 2016 to 2020, the lowest RCI value was 0,2917 and the highest value was 3,156. While the RCI value for 2020 to 2024 had the lowest value of 0.3862 and the highest was 2,1791. Based on the RCI value, it is divided into 3 classes, low, medium, and high, in order to represent the intensity of change in each village. Based on the results of statistical calculations, it can be concluded that there is a strong influence between the JJLS variable and the growth of built-up land in the research area.